THE EFFECTIVENESS OF FAIRY TALES MAZE FOR TEACHING READING COMPREHENSION AT THE FIRST GRADE STUDENTS OF SMA ISLAM USWATUN HASANAH IN ACADEMIC YEAR 2018/2019 - Masyudi Masyudi (Mandala, 2019)
This research aimed to find out the effectiveness of fairy Tales Maze for Teaching Reading Comprehension at the first grade students of SMA Islam Uswatun Hasanah in academic year 2018/2019. The method of this research was pre-experimental research (quantitative method). The population of this research was the students of SMA Islam Uswatun Hasanah in academic year 2018/2019. The sample of the study was 28 students consist of one class. The sample technique used in this was lottery technique sampling. The technique which was used to analysis the data was t-test formula. From the research data found out that the students` t-test score is (4.875) and t-table (2.052) from (df) 27. Based on the result of the study, it can be concluded that the use of Fairy Tales Maze has positive effect in teaching reading comprehension at the first grade students of SMA Islam Uswatun Hasanah in academic year 2018.2019.